Penerapan Model Problem Based Learning (PBL) terhadap Hasil Belajar Matematika Siswa Kelas V SDN 166 Rejang Lebong - Jesika, Vio; Fitriyana, Nur; Abadi, Candres (Journal of Elementary School (JOES), 2024)
This research aims to determine the difference in students' average scores before and after using the Problem Based Learning (PBL) learning model, and to determine the differences in Mathematics learning outcomes for class V students at SDN 166 Rejang Lebong. The method used in this research was pure experimentation and the research subjects were all class V students at SDN 166 Rejang Lebong. The instrument used is test questions. The research results show that the average pre-test score is 8.04. After being given treatment using the Problem Based Learning (PBL) model in class, the average post-test score increased to 83.27. The results of this research conclude that there is a difference in the average student scores before and after using the Problem Based Learning learning model. Keywords: Learning Outcomes, Explanation, Problem Based Learning (PBL).